Second promised land : migration to Alberta and the transformation of Canadian society - Hiller, Harry H., 1942- (McGill-Queen's University Press, 2009)
Combining statistical analysis and ethnographic study, Harry Hiller uncovers two waves of in-migration to Alberta. His innovative approach begins with the individual migrant and analyzes the relocation experience from origin to destination. Through interviews with hundreds of migrants, Hiller shows that migration is complex and dynamic, shaped not just by what Alberta offers but also prompted by a process that begins in the region of origin which makes migration possible, and helps determine whether migrants stay or return home. By combining a social psychological approach with structural factors such as Alberta's transition from a regional hinterland province to its emerging role the global system, discussions of gender, the internet, and folk culture, Second Promised Land provides a multi-dimensional and deeply human account of a contemporary Canadian phenomenon.